Endoscopically Documented Response in Chronic Duodenal Ulcer: A Case Report (Advancements in Homeopathic Research, 2022)
A case of chronic duodenal ulcer with few erosions and gross deformity of first part of duodenum, successfully managed by homoeopathic treatment with objective evidence of improvement (by Endoscopy) is presented. The basis of the prescription and details of follow up are provided. Some special aspects of the case are also discussed
Keywords: Chronic duodenal ulcer; Homoeopathy; Documentation; Anacardium orientale; Sulphur; Nux vomica